The effect of the administration of vitamin K2 to the pregnant women on the activities of prothrombin group in cord blood. - Rahajuningsih D. Setiabudy Rahajuningsih D. Setiabudy (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Hemorrhagic disease of the newborn (HDN) is a hemorrhage at the neonatal period. The most dangerous form of HDN is intracranial bleeding which may be fatal. The most frequent cause of HDN is deficiency of vitamin K dependent factors or prothrombin group.Objective: The aim of the study is to know the effect of the administration of vitamin K2 to the pregnant women on the activities of prothrombin gourp in cord blood.Methods: This was experimental design. Forty pregnant women were enrolled in this study. Vitamin K2 was given orally at the dosage of 10 mg twice daily. At delivery the cord blood was collected for the measurement of prothrombin group activities.Results: In the treatment group the median activities of prothrombin were 37.3%, F VII were 62.4%, F IX were 29.5%, and F X were 34.9%, while in the control group the median activities of prothrombin were 33.5%, F VII were 47.3%, F IX were 23.7%, and F X were 29.0%. The difference of the activities of vitamin K dependent factors between treatment group and control group was statistically significant. Conclusion: The administration of vitamin K2 to the pregnant women increases the activities of vitamin K dependent factors in the cord blood.Key words: hemorrhagic disease of the newborn - oral vitamin K2 - cord blood - vitamin K dependent factor activity